Margin regulation and volatility - Johannes Brumm; Felix Kubler; Michael Grill; Karl Schmedders (European Central Bank (ECB), 2014)
In this paper we examine the quantitative effects of margin regulation on volatility in asset markets. We consider a general equilibrium infinite-horizon economy with heterogeneous agents and collateral constraints. There are two assets in the economy which can be used as collateral for short-term loans. For the first asset the margin requirement is exogenously regulated while the margin requirement for the second asset is determined endogenously. In our calibrated economy, the presence of collateral constraints leads to strong excess volatility. Thus, a regulation of margin requirements may have stabilizing effects. However, in line with the empirical evidence on margin regulation in U.S. stock markets, we show that changes in the regulation of one class of assets may have only small effects on these assets' return volatility if investors have access to another (unregulated) class of collateralizable assets to take up leverage. In contrast, a countercyclical margin regulation of all asset classes in the economy has a very strong dampening effect on asset return volatility.
Keywords: D53; G01; G12; G18; 330; collateral constraints; general equilibrium; heterogeneous agents; margin requirements; Regulation T